COMPARISON OF KAJJALI PREPARED BY TRADITIONAL AND MODERN METHODS - Ajaghen, Seeneevassen; Madhuri, Nagras (International Journal of Ayurveda and Pharma Research, 2015)
Background: In the present study, Kajjali (black sulphide of mercury) has been prepared by two different methods. The first method is the traditional method in which the purified mercury and sulphur are rubbed in a clean Khalva (earthen vessel) for approximately 24 to 30 hours until the Kajjali is formed. The second method which is also referred to as the modern method involves the use of a grinder to facilitate the formation of Kajjali. Aim & Objective: The products from the two methods are then compared by assessing different organoleptic, alchemical and physicochemical parameters. Materials & Methods: There are different proportions of purified Parada (Mercury) and Gandhaka (Sulphur) mentioned in the Ayurvedic texts for the preparation of Kajjali. The present work was aimed at the preparation and standardization of Samagunabalijarita Kajjali (equal parts of purified Mercury and Sulphur) by both the traditional and the modern methods. Result and conclusion: It was found that both the methods yielded Kajjali possessing similar attributes and qualities.